THE EVOLUTION OF DIGITAL LEADERSHIP RESEARCH: A SYSTEMATIC LITERATURE REVIEW ON EMPLOYEE PERFORMANCE - Asri Winanti Madyoningrum; Gibson Manalu (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
A comparative analysis of five empirical studies reveals a complex pattern of findings regarding the influence of digital leadership on employee performance. Consensus suggests that in corporate and manufacturing contexts, digital leadership has a significantly positive effect, particularly when mediated by increased organizational commitment and employee empowerment. However, this finding is not universal. Studies in the public sector show that digital leadership does not have a significant direct effect, indicating that the bureaucratic context and organizational readiness are critical limiting factors. Furthermore, its effectiveness has been shown to depend on contingency factors such as employee digital literacy and the quality of the organization's digital culture, which can act as either enablers or inhibitors. Therefore, it can be concluded that the success of digital leadership depends heavily on the alignment between leader competencies, subordinate digital capabilities, and the organizational culture's readiness for transformation.